Let's solve each of the equations step by step.
1. Solve \( x^2 + 6x + 9 = 0 \)
This is a perfect square trinomial:
\[ (x + 3)^2 = 0 \]
Taking the square root of both sides, we find:
\[ x + 3 = 0 \implies x = -3 \]
2. Solve \( 16x^2 - 49 = 0 \)
This can be factored as a difference of squares:
\[ (4x - 7)(4x + 7) = 0 \]
Setting each factor to zero gives us:
\[ 4x - 7 = 0 \implies 4x = 7 \implies x = \frac{7}{4} \] \[ 4x + 7 = 0 \implies 4x = -7 \implies x = -\frac{7}{4} \]
Listing smaller solution first:
\[ x = -\frac{7}{4}, \frac{7}{4} \]
3. Solve \( 3x^2 + 18x + 24 = 0 \)
First, simplify the equation by dividing all terms by 3:
\[ x^2 + 6x + 8 = 0 \]
Now, factor the quadratic:
\[ (x + 2)(x + 4) = 0 \]
Setting each factor to zero gives us:
\[ x + 2 = 0 \implies x = -2 \] \[ x + 4 = 0 \implies x = -4 \]
Listing smaller solution first (remembering we should reverse to smaller first):
\[ x = -4, -2 \]
4. Solve \( 2x^2 + x = 5 \)
Rearranging the equation:
\[ 2x^2 + x - 5 = 0 \]
Now apply the quadratic formula:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] where \( a = 2, b = 1, c = -5 \):
Calculating the discriminant:
\[ b^2 - 4ac = 1^2 - 4 \cdot 2 \cdot (-5) = 1 + 40 = 41 \]
Now substitute into the quadratic formula:
\[ x = \frac{-1 \pm \sqrt{41}}{4} \]
Calculating the two solutions:
- \( x_1 = \frac{-1 + \sqrt{41}}{4} \)
- \( x_2 = \frac{-1 - \sqrt{41}}{4} \)
Calculating \( x_2 \) in decimal to the hundredths:
\[ \sqrt{41} \approx 6.403 \implies x_2 \approx \frac{-1 - 6.403}{4} \approx \frac{-7.403}{4} \approx -1.85075 \approx -1.85 \]
So, listing smaller solution first, we have:
\[ x = \frac{-1 - \sqrt{41}}{4} \text{ (around -1.85)}, \frac{-1 + \sqrt{41}}{4} \]
5. Finding zeros of \( y = 2x^2 + 7x \)
Set \( y = 0 \):
\[ 2x^2 + 7x = 0 \]
Factoring out \( x \) gives us:
\[ x(2x + 7) = 0 \]
Setting each factor to zero gives us:
- \( x = 0 \)
- \( 2x + 7 = 0 \implies 2x = -7 \implies x = -\frac{7}{2} \)
Listing smaller solution first:
\[ x = -\frac{7}{2}, 0 \]
Summary of Solutions
- \( x = -3 \)
- \( x = -\frac{7}{4}, \frac{7}{4} \)
- \( x = -4, -2 \)
- \( x = \frac{-1 - \sqrt{41}}{4}, \frac{-1 + \sqrt{41}}{4} \approx -1.85 \)
- \( x = -\frac{7}{2}, 0 \)